EFEKTIVITAS PREEMTIF KETAMIN SUBDOSIS DALAM MENGURANGI KEBUTUHAN OPIOID INTRAOPERATIF DAN WAKTU EKSTUBASI - Rizky Bagoes Septyawan (Jurnal Ilmiah Kesehatan Media Husada, 2021)
Surgical perioperative management undergoes updates to support postoperative patient outcomes. The concept of longer preoperative fasting times, cleansing ofthe gastrointestinal tract, and re-feeding after 3-5 days after surgery has begun to be abandoned which is then formulated into a new protocol called ERAS(Enhanced Recovery After Surgery) including preoperative counseling, optimization of nutrients, the use of standard anesthesia and analgesy drugs, as well asearly mobilization using the concept of preemptive analgesia. The use of low-dose ketamine for postoperative analgesia has evolved in part due to nmdaantagonistic properties that reduce central sensitization and opioid tolerance but are still controversial. This study aims to study the effects of low-dose ketamineas a preemptive and evaluate the total needs of opiods, as well as the length of time extubation with single blind experimental research. Patients with label A gotpreemptive therapy of subdose ketamine while label B got perioperative standard analgesia therapy. Analgesia in groups A and B is administered before surgery.Treatment control is done with single blind control that is the patient does not know the type of drug given. The comparison of the amount of fentanyl in the controlgroup and treatment in this study was significantly different (p=0.044). The old comparison of extubation in both groups obtained a significant p value (<0.0001).Preemptive administration of subdose ketamine effectively decreases the amount of fentanyl administration used during surgery and shortens the extucation time. Keywords: Preemptive; Ketamin subdose; Fentanil; Extucation Time.